If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + x = 32 + -1x Solving 6 + x = 32 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 6 + x + x = 32 + -1x + x Combine like terms: x + x = 2x 6 + 2x = 32 + -1x + x Combine like terms: -1x + x = 0 6 + 2x = 32 + 0 6 + 2x = 32 Add '-6' to each side of the equation. 6 + -6 + 2x = 32 + -6 Combine like terms: 6 + -6 = 0 0 + 2x = 32 + -6 2x = 32 + -6 Combine like terms: 32 + -6 = 26 2x = 26 Divide each side by '2'. x = 13 Simplifying x = 13
| 9x-x=40 | | 5x+2(x+8)-6(4x-5)= | | -3x^2+7x=-10 | | 8xy+6yz-4xz-8xy= | | -47-18=13a | | -1(z-6)=-20 | | -7+8x=19x+15 | | -p=2 | | -6x+9=3x-27 | | (y+3)(y+5)= | | (3b^3+9b^2-3)+(2b^3-9b+7)= | | (15-7)x=(11+5)x | | -9=9(y+3) | | 3x+4(2-x)=4x+5 | | 4(2x)=72 | | (x^3+x^2+x+1)(5x-3)= | | 2(3+4)-6=48 | | 6x+4=24 | | 2(4x)=40 | | 9x-7+2x=8x+5-5x | | -x^2-x+2=0 | | (7x+5)(5x^2+8x+6)= | | 16x=-48 | | 0.8w-0.6+0.3w=3 | | (x^2-3x+4)(2x-1)= | | 6x+4= | | 7x+8x=105 | | 4(w-5)=12 | | -3(t-5)=2(t-5) | | 7t^2(t-t^2+5t^3)= | | 17-4n=-7(-7n-4n) | | y=200+7x |